2019
DOI: 10.1097/ftd.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Self-Sampling by Guardians of Children With Epilepsy Is Feasible: Comparison With Plasma for Multiple Antiepileptic Drugs

Abstract: Possibilities of dried blood spots as a matrix in therapeutic drug monitoring of antiepileptic drugs in children THESIS FOR DOCTORAL DEGREE (Ph.D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…25 In an earlier study, we showed that parents in this group can collect blood samples with as good quality as the nurses. 9 In this study, we found that the parents also need to be prepared for a new role in the sampling situation. The education can be improved by informing about how the parent can prepare the child and him/herself for this new situation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…25 In an earlier study, we showed that parents in this group can collect blood samples with as good quality as the nurses. 9 In this study, we found that the parents also need to be prepared for a new role in the sampling situation. The education can be improved by informing about how the parent can prepare the child and him/herself for this new situation.…”
Section: Discussionmentioning
confidence: 92%
“…The parents managed to collect a sample, acceptable for analysis. 9 With respect to children with diabetes, several reports have provided insight into improved patient involvement by web-education, 10 effects of education interventions in children with diabetes 11 and opinions on technology solutions to improve knowledge. 12 However, no earlier studies on dried blood spot collection have focused on the more qualitative aspects of self-sampling at home.…”
mentioning
confidence: 99%
“…Because DBS is now being increasingly recognized as a great option to collect blood samples (Dittakavi, Jat, & Mullangi, 2019; Kim, Park, Long, Kim, & Kwon, 2019; Kumar Saini et al, 2019; Linder et al, 2019; Sulochana, Daram, Srinivas, & Mullangi, 2019), we were interested in developing and implementing a novel strategy for carrying out ISR analysis using quarter‐, half‐ and full‐DBS discs. As depicted in the Figure 1, this framework of dividing DBS cards (into two equal pieces or four equal pieces, as the case may be) would render itself as a useful approach for preparing aliquots of study samples collected on DBS cards for ISR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There are different methods (GC, LC, HPLC, High Performance Thin Layer Chromatography (HPTLC), LC-MS/MS, UHPLC-MS/MS, SFC-ESI-MS/MS) to measure the level of CBZ and its major metabolite in biological samples of epilepsy patients treated with this AED in monotherapy or polytherapy. The presented methods use biological samples such as: Plasma [47][48][49][50][51][52][53][54][55], serum [53,[56][57][58], urine [47,59], saliva [60], dried saliva [61] and respiratory condensate [62,63], dried blood spot [20,64,65]. In TDM of CBZ, plasma, serum, and urine are the most commonly used.…”
Section: Carbamazepinementioning
confidence: 99%